PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN DAN MEKANISME TATA KELOLA PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Putri, Ida Ayu Sasmika; Suprasto H, Bambang (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of corporate social responsibility and corporate governance mechanisms on the value of the company. Samples were selected using purposive sampling method and acquired 60 companies . Testing the hypothesis in this study was done by using multiple linear regression analysis . This study obtained results that corporate social responsibility, managerial ownership , institutional ownership, board of directors , audit committee and board of directors simultaneously positive effect on firm value . Corporate social responsibility is partially positive effect on the value of the company and corporate governance mechanisms are in proxy with managerial ownership, institutional ownership, board of directors, audit committee and board of directors partially positive effect on firm value .
Keywords: Value of The Company, Corporate Social Responsibility and Corporate Governance Mechanisms